System Improvement Proposal in Increasing the Service Quality of Online Warehouse Administration System using ISO/IEC 9126 Standard (Case Study: PT. PLN (PERSERO) Duri Rayon) - Muhammad Ihsan Hamdy; Rika Rahmat Putri (Jurnal Rekayasa Sistem & Industri, 2020)
In building a system, it was needed a quality guarantee. A system could be stated wellqualified, if it met the user needs. The quality could be measured from various points of views.One point of views to measure the software quality was focusing on user satisfaction (userbased). To know the quality of a system, it was needed a quality analysis of its system. Therewas a lack of service when online warehouse administration system used to manage thewarehouse material inventory in PT. PLN (Persero) Duri Rayon was used. This research aimedat finding proposed improvements for increasing the service quality percentage of onlinewarehouse administration system based on ISO/IEC 9126 standard. The methods of collectingthe data were using interview and questionnaire to know user complaints to the user. MaturityModel and Delay approaches were used to process the data. In testing the reliability level,online warehouse administration system was on the first level (the system was computerized,but it was not standardized yet). In testing the delay, all the delays in input were on goodcategory and it could be understandable. Based on the levels of maturity and delay, the testshowed that there was a need to improve and maintenance the online warehouse administration system to increase the performance of system service quality for users, so that the existence ofrepairs and maintenance systems can increase 26% to 41% the percentage of the quality of aninformation technology system.